Southwest Airlines flight 1248 (A) - Diermeier, Daniel, (SAGE Knowledge. Cases., 2017)
After the companys first aviation fatality, Southwest Airliness CEO is faced with new and difficult decisions. The alacrity and compassion that characterized the companys response serves as a paradigm for any organization facing a future crisis situation.